Maximizing Global Cooling Potential in Carbon Dioxide Removal (CDR) Procurements: A Proposal for Tonne-Year Pricing - Wenger, Samuel; D'Alessandro, Deanna; Wright, Christopher (Frontiers in Climate, 2022)
Recently, a consortium of companies including Stripe, Alphabet, Shopify, Meta, and McKinsey allocated US$925 million for advanced market commitments to kickstart the early-stage Carbon Dioxide Removal (CDR) market. We argue that it is now more important than ever to consider a Global Cooling Potential (GCP) perspective in corporate CDR procurements. Currently, CDR projects are evaluated and priced on a simple cost-per-tonne basis, which fails to monetize storage duration and can ultimately incentivize the large-scale procurement of short-duration CDR. However, the relative duration of carbon storage is a critical aspect of any CDR project given the implications for climate warming from growing atmospheric concentrations of carbon dioxide. In this perspective article, we apply tonne-year carbon pricing to Microsoft and Stripe’s initial CDR procurements to demonstrate that a combination of tonne-year pricing and conventional pricing could produce a CDR portfolio that simultaneously prioritizes storage duration, volume, and temporal urgency, which are all important considerations for maximizing GCP.